Do Birds of a Playful Feather Flock Together? Playfulness and Assortative Mating - Chick, Garry; Proyer, Rene; Purrington, Andrew; Yarnal, Careen (American journal of play, 2020)
The authors discuss assortative mating, the tendency--important for increased genetic variation--of individuals to mate with the phenotypically similar at rates greater than chance. Influenced by many factors--physical characteristics like height and weight and demographic elements like behavior and attitudes, economic status and education, church attendance and ethnic identity, politics and personality--assortative mating has been considered with regard to having a good sense of humor but never to being playful or being fun loving. Based on a study of 254 undergraduates, the authors examine how these variables correlate with the search for desirable mates by adults and suggest the variables are indeed subject to assortative mating. Key words: assortative mating, fun loving, mate choice, playfulness, sense of humor, social homogamy